The Impact of Product Quality, Social Media Marketing, and Customer Relationship on Customer Loyalty through Customer Satisfaction: A Case Study of Putri Chaniago Furniture - Finola Fiftem Eka Putri; Yulasmi Yulasmi; Mardhatila Fitri Sopali (STIE Amkop Makassar, 2024)
This study examines the influence of product quality, social media marketing, and customer relationship on customer loyalty through customer satisfaction in the context of Putri Chaniago Furniture. The research findings reveal several significant relationships. Firstly, product quality demonstrates a positive and significant impact on customer satisfaction, indicating the importance of delivering high-quality products to enhance customer satisfaction. Secondly, while social media marketing positively affects customer satisfaction, its impact is found to be nonsignificant, suggesting the need for further exploration of social media strategies for improving customer satisfaction. Thirdly, customer relationship exhibits a positive and significant influence on customer satisfaction, highlighting the importance of fostering strong relationships with customers to enhance satisfaction levels. Furthermore, all three factors—product quality, social media marketing, and customer relationship—positively and significantly affect customer loyalty through customer satisfaction, underscoring their collective importance in driving customer loyalty. These findings suggest that companies should prioritize efforts to improve product quality, optimize social media marketing strategies, and strengthen customer relationships to foster customer loyalty. Future research endeavors could explore additional variables and expand the scope of analysis to gain deeper insights into customer loyalty dynamics. Additionally, enhancing sample sizes, utilizing updated data, and broadening the research scope are recommended for ensuring the relevance and accuracy of future studies.